Water Quality and Some Pesticide Residues in Nam Ton of Sangthong District, Vientiane Capital - Deevanhxay, Phengxay; Phomkeona, Kesiny; Sengthongsa , Budda; Thaiphachanh, Keomany (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
This research aimed to analyze the general water quality, toxic element, and pesticide residues such as organochlorine and organophosphate pesticides in Nam Ton river, Sangthong district, Vientiane Capital, Laos. The water samples were collected from the upper and lower areas of the banana plantation site, which consisted of five points. Several physical and chemical parameters such as temperature, pH, EC, DO, Turbidity, CODCr, PO43-, NO3--N, Toxic element (Pb, Cd, As, Hg), and pesticides (organochlorine 22 mixed and organophosphate 2 mixed) were analyzed. The study found that most of the water quality parameters were in the criteria of surface water standard in category 3 of the national environmental standards 2017. However, DO value at point 2, PO43- at point 4, and most of CODCr value were out of range of the standard value. Endosulfan sulfate and 4.4'-DDT residues were found at 0.12 - 0.22 µg/L and 0.3 - 0.31 µg/L in three samples (points 2, 3 and 4). 4.4'-DDE residue was found at 0.02 µg/L in the sample of point 2. This indicates that these pesticides may have been used in the area in the past or at present, but they were low concentration and within the national environmental standard values. For the organophosphate pesticides, only chlorpyrifos were found at 0.05 - 0.64 µg/L in all five sampling points, possibly because chlorpyrifos was commonly used in the cultivation of leafy vegetables. The residues may be washed into the river, but this compound is not yet defined in Lao national environmental standards.